Main predictors of in-hospital adverse outcomes in non-ST elevation acute coronary syndrome patients with multivessel disease - Yu. N. Neverova; R. S. Tarasov; O. A. Nagirnyak (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To evaluate the range of risk factors associated with adverse cardiovascular events onset in hospital period of follow-up in patients with non-ST elevation acute coronary syndrome (NSTEACS) with multivessel disease (MD).Material and methods. To the study, under the framework of prospective, single-center registry, the NSTEACS and MD patients were included. Depending on the strategy of revascularization, three groups were selected: staged PCI, coronary bypass (CBG) and PCI as the first with CBG as the second stage. As adverse cardiovascular events, the following were taken: death, myocardial infarction, stroke or transient cerebral ishemia, clinically significant bleeding by BARC, repeat nonscheduled revascularization of target vessel. Results. Analysis revealed the groups of factors increasing the probability of adverse cardiovascular events. Those are: (1) clinical and demographic  — older age, diabetes, postinfarction cardiosclerosis, multifocal atherosclerosis, chronic renal failure; (2) coronary and surgical — left main stem lesion, severe atherosclerosis by SYNTAX Score, high surgical risk by EuroScore II, revascularization strategy;  (3) predominance of low or moderate risk by GRACE comparing with high risk.Conclusion. The results have confirmed high predictional significance of clinical and demography and coronary factors for development of adverse cardiovascular diseases. A significant finding of the study was the fact that in a hospital with surgery and endovascular treatment available 24/7, the intermediate and low GRACE risk in NSTEACS and MD is a factor of adverse cardiovascular events development due to revascularization delays if the risk is not high.